KORELASI PEMBELAJARAN AQIDAH AKHLAK TERHADAP AKHLAK SISWA DI MAN 1 BOGOR - Saventy, Tiara Ayu (EDUTECH CONSULTANT, 2019)
This research was conducted for approximately 2 months, namely February to March 2019 which was held at the Bogor 1 State Islamic Senior High School. This research method uses quantitative methods, with data collection techniques namely questionnaires, observation and documentation. The respondents of this study were determined randomly. Data collection by means of questionnaires was given to respondents who were selected at random, while the technique of collecting data by school observation. Then the data is processed with IBM SPSS statistical data. The purpose of this study is (1) To analyze the learning of moral aqidah in Bogor 1 State Islamic Senior High School. (2) To find out the morals of students in Bogor 1 State Islamic Senior High School. (3) To analyze the learning correlation of Aqidah Akhlak to the morals of students at Madrasah Aliyah Negeri 1 Bogor. From the results of the study Correlation of Aqidah Akhlak Learning to Students in MAN 1 Bogor. The relationship or relationship between Aqiah Learning Morals to Student Morals in MAN 1 Bogor. From the calculation it has been obtained rxy 0.519 it turns out to be located between 0.400-0.599.